Cooperation of Hot Holes and Surface Adsorbates in Plasmon-Driven Anisotropic Growth of Gold Nanostars - Guo, Wenxiao (J Am Chem Soc, 2020)
Light-driven synthesis of plasmonic metal nanostructures has garnered broad scientific interests. Although it has been widely accepted that surface plasmon resonance (SPR)-generated energetic electrons play an essential role in this photochemical process, the exact function of plasmon-generated hot holes in regulating the morphology of nanostructures has not been fully explored. Herein, we discover that those hot holes work with surface adsorbates collectively to control the anisotropic growth of gold (Au) nanostructures. Specifically, it is found that hot holes stabilized by surface adsorbed iodide enable the site-selective oxidative etching of Au(0), which leads to nonuniform growths along different lateral directions to form six-pointed Au nanostars. Our studies establish a molecular-level understanding of the mechanism behind the plasmon-driven synthesis of Au nanostars and illustrate the importance of cooperation between charge carriers and surface adsorbates in regulating the morphology evolution of plasmonic nanostructures.